Evaluation of The Quality of Antibiotic Use in Urinary Tract Infection Patients in hospitalization installations of NTB Provincial Hospital in 2019 - Husnul Marifah; Candra Eka Puspitasari; Ida Ayu Eka Widiastuti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Urinary Tract Infection (UTI) is a nosocomial infection with several occurrences around 39-60 % in Indonesia. Antibiotics are the main therapy for UTIs. The use of poor quality antibiotics can cause irrational antibiotics therapy which leads to the risk of resistance. This research aims to recognize the patterns of antibiotics use and determine the percentage of the appropriate use of antibiotics. This research is an observational type of research with a cross-sectional design. The data were obtained retrospectively from July to September 2021 using 53 medical records of UTI hospitalized patients. The obtained data were analyzed descriptively and quantitatively using the Gyssens method. The result shows the characteristics of UTI patients are dominated by males (54,72%) and occurred in toddlers at age of 0 -5 years (20,75%) and the elderly at age 56- 65 years (15,09%). The antibiotics used in this research were dominated by ceftriaxone (37,50%). Of 53 patients using 80 antibiotics, the percentage of use accuracy of antibiotics in UTI patients in RSUD Provinsi NTB (category 0) is 23,75%. The inappropriate use of antibiotics is 76,25% was found in various categories, namely category VI medical record data incomplete (32,50%), IVA where there were more effective antibiotics (10%), IVC there were cheaper antibiotics (1,25%), IIIA too long duration of antibiotics use (8,75%), IIIB too short duration of antibiotics use (7,50%), IIA improper dosage of antibiotics (11,25%), and IIB improper giving interval (5%). Therefore, it can be concluded that there is still irrational use of antibiotics, especially improper dosage category.